Struktura kosztów produkcji i cen surowców mineralnych jako kryterium międzynarodowego socjalistycznego podziału pracy w gałęziach surowcowych - Podobiński, Andrzej (Wydział Prawa i Administracji UAM, 1977)
Decisions connected with specialization of production on an international scale should be based on the comparison of the costs of production of goods in the countries entering such international co-operation. The costs of production will become a conclusive base of prices in the international trade and of the development of the economic integration of the socialist countries only after unification of the methods of calculating the costs of production and after establishment of such rates of exchange that will represent the relative value of the currencies in the countries associated in the Council for Mutual economic Aid. For the mineral raw materials the structures of their prices in respective socialist countries are essentially different. The analysis of the problem shows that efforts must be continued to make uniform the structures of costs of production and prices of mineral raw materials, in order to obtain the comparability of these costs and prices.
The Structure of the Costs of Production and Prices of Mineral Raw Materials as the Criterion of International Socialist Division of Labour in the Raw Material Branches